HEAT EXCHANGER DESIGN FOR THE GOLD NANOPARTICLES PRODUCTION IN INDUSTRIAL SCALE - Asep Bayu Dani Nandiyanto; Risti Ragadhita; Teguh Kurniawan; Erlangga, Thyta Medina Salsabila (Politeknik Negeri Banyuwangi, 2023)
This study aims to develop and analyze the design of heat exchangers in the production of gold nanoparticles (AuNPs) by the biosynthesis method using Sargassum horneri (SH) extract. The simple design of this heat exchanger (HE) uses the shell and tube type, the one-pass tube, and the fluids are water. Other specifications for a HE design are the tube length is 4.267 m, the shell diameter is 254 mm, the outer tube diameter is 22.225 mm, the inner tube diameter is 21.184 mm, the wall thickness is 2.1082 mm, and the pitch tube is 31.75 mm. Based on manual calculations using Microsoft Excel software, the results show that this design has laminar flow as indicated by the Reynolds value. In addition, the HE designs has an effectiveness value of 98.98% with an NTU value of 11.50. In this study, the HE designs results have a high effectiveness value, so it can be considered effective for use in producing gold nanoparticles with SH extract. Therefore, this HE designs analysis can be used as a learning medium in the HE designs process, the operating mechanism, and the performance analysis of the HE.